Bhagavad Gita’s vision for a Harmonious Society: Ethics, Values and Social Justice - Syamala K. (Methexis)
Gita emphasizes on the necessity of ethics and deals with moral order maintaining peace, harmony and social order- It highlights the notion of desireless actionIn its message, the Gita advises individuals to take up a life of action and recommends renunciation in action rather than renunciation of action- Gita insists that a man should shape his ideals according to the station of his life in society or follow his Swadharma – The central point of the teaching of Bhagavad Gita is Nishkama karma – this ideal is realized by performing selfless action- In Gita, we can see the description of the man who has attained perfect state or sthitaprajňa – A yogi is sthitaprajňa who is firmly rooted in higher reason and unmoved by passions and emotions – This karma yogi has to work for the benefit of humanity in a spirit of detachment- Here the yogi has no selfish motives but works for the preservation and welfare of society- This is called Lokasamgraha – This philosophy of action advocated by Gita holds that every individual has to be engaged in some action and in the absence of it, life becomes meaningless.